The art of happiness at work A handbook for living - The Dalai Lama and Howard C. Cutler ([London] Hodder Paperback, 1998)
The Dalai Lama is probably one of the only people who, if you ask him if he's happy, even though he's suffered the loss of his country, will give you an unconditional "yes." What's more, he'll tell you that happiness is the purpose of life, and the "the very motion of our life is toward happiness." How to get there has always been the question. He's tried to answer it before, but he's never had the help of a psychiatrist to get the message across in a context we can easily understand.
Includes Bibliographies 269p.
Keywords: Work--Psychological aspects